Frequency-Uniform Decomposition, Function Spaces Xp, qs, and Applications to Nonlinear Evolution Equations. (10th July 2013) - Ru, Shaolei; Chen, Jiecheng
Abstract : By combining frequency-uniform decomposition with L p (ℓ q ), we introduce a new class of function spaces (denoted by X p, q s ). Moreover, we study the Cauchy problem for the generalized NLS equations and Ginzburg-Landau equations in L r ( 0, T ; X p, 1 s ) .